Embedding landfill diversion in economic, geographical and policy settings panel based evidence from Italy - Massimiliano Mazzanti; Anna Montini; Francesco Nicolli (Fondazione Eni Enrico Mattei (FEEM), 2008)
This paper analyses the process of delinking for landfilling trends embedding the dynamics in a frame where economic, geographical and policy variables enter the arena We aim at investigating in depth what main drivers may be responsible for such a phenomenon, and whether differences may be observed focusing the lens on a decentralised provincial based setting. We exploit a rich panel dataset stemming from Official sources (APAT, Italian environmental agency) merged with other provincial and regional based information, covering all the 103 Italian provinces over 1999-2005. The case study on Italy is worth being considered given that Italy is a main country in the EU. Thus it offers important pieces on information on the evaluation of policies. Evidence shows that the observed decoupling between economic growth and landfilling is driven by a mix of structural factors, as population density and other waste management opportunity: local opportunity costs and landfill externalities matter in shaping waste policies and local commitment to landfill diversion. But not only structural factors are relevant. If on the one hand landfill taxation is a significant driver of the phenomenon, even at the more coherent regional level, where the tax is implemented, waste management instruments, when we exploit the provincial dataset, are associated to high significant negative effect on landfilled waste. A good performance on managing waste according to economic rationales helps reducing the amount that is landfilled. In association to the features of the tariff system, we also underline the key role played by the share of separated collection. Both the evolution of collection and tariff system are joint factors that may drive a wedge between the comparative waste performances of northern and southern regions. We finally note that lock in effects linked to the intensity of incinerator sites in the area are relevant for landfilling: past investments in incineration lock in the region in this technological path, which may be associated to less opportunity cost and lower external effects. Summing up, landfill diversion is stronger where the economic cost deriving from high population density, a structural factor, are higher, and waste management collection systems and economic instruments are associated with higher performances.
Keywords: C23; Q38; Q56; 330; Landfill Policies; Incineration; Landfill Tax; Policy Effectiveness; Waste Management; Delinking; Landfill Trends; Kuznets Curves